2018
DOI: 10.3389/fpsyg.2018.00517
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cultures and the Psychological Geography of Switzerland: Person–Environment–Fit in Personality Predicts Subjective Wellbeing

Abstract: The present study extended traditional nation-based research on person–culture–fit to the regional level. First, we examined the geographical distribution of Big Five personality traits in Switzerland. Across the 26 Swiss cantons, unique patterns were observed for all traits. For Extraversion and Neuroticism clear language divides emerged between the French- and Italian-speaking South-West vs. the German-speaking North-East. Second, multilevel modeling demonstrated that person–environment–fit in Big Five, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 137 publications
(260 reference statements)
3
54
2
Order By: Relevance
“…However, complex psychological phenomena-such as loneliness-are unlikely to be fully explained by a few strong (individual-level) predictors (Matz, Gladstone, & Stillwell, 2017). Recent studies have shown that regional characteristics play a distinct role for individual-level psychological functioning (e.g., Jokela, Bleidorn, Lamb, Gosling, & Rentfrow, 2015;Götz, Ebert, & Rentfrow, 2018). We therefore suggest broadening the perspective on loneliness.…”
Section: In a Lonely Place: Investigating Regional Differences In Lonmentioning
confidence: 91%
“…However, complex psychological phenomena-such as loneliness-are unlikely to be fully explained by a few strong (individual-level) predictors (Matz, Gladstone, & Stillwell, 2017). Recent studies have shown that regional characteristics play a distinct role for individual-level psychological functioning (e.g., Jokela, Bleidorn, Lamb, Gosling, & Rentfrow, 2015;Götz, Ebert, & Rentfrow, 2018). We therefore suggest broadening the perspective on loneliness.…”
Section: In a Lonely Place: Investigating Regional Differences In Lonmentioning
confidence: 91%
“…show that regional personality does not only bear on an individual's psychological adjustment and physical health (Bleidorn et al, 2016;Ebert, Gebauer, Talman, & Rentfrow, 2020;Götz et al, 2018) but also on an individual's behavior. On a more general theoretical level, we further argue that our results offer good reason to reassess the role of personality in widely used interactionist accounts of behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The wording of the other item for openness was 'has an active imagination'. Cronbach's alpha for openness was .61, which is acceptable for a two-item scale (Brailovskaia & Margraf, 2018;Götz, Ebert, & Rentfrow, 2018;Whaite, Shensa, Sidani, Colditz, & Primack, 2018). In taking a 2-item scale, we assess only the aesthetic and imaginative aspects of openness to experience.…”
Section: Personalitymentioning
confidence: 99%